APPROACHES TO TEACHING UZBEK TO YOUNG LEARNERS USING A BILINGUAL METHOD (Global Conference on Multidisciplinary Research and Innovation, 2026)
This thesis examines the effectiveness of the bilingual method in teaching Uzbek to young and foreign learners. Based on C. J. Dodson’s framework, the study highlights the strategic use of the learners’ mother tongue to support comprehension, oral proficiency, and vocabulary development. By integrating the stages of presentation, practice, and production, the bilingual method enables efficient explanation of linguistic content and increases learner motivation. The findings suggest that the bilingual method is an effective approach for developing functional bilingualism and improving overall language learning outcomes in Uzbek language instruction.
Keywords: bilingual method; Uzbek language teaching; bilingual education; medium of instruction; mother tongue (L1); second language acquisition; young learners; content-based language teaching.